El arte último del siglo xx and El arte en la era de lo global: two key texts to understand contemporary artistic creation (REVISTA NODO, 2024)
The emeritus professor in Art History at the University of Barcelona, ​​Anna Maria Guasch, published in 2016 her latest major historical and theoretical study on the artistic, theoretical and curatorial production of art closest to our time. We are referring to Art in the Global Era, 1989-2015, a study that becomes the continuation of the cartography inaugurated with The Last Art of the 20th Century. From postminimalism to multiculturalism (2000), both published by Alianza (Madrid). Despite the continuity that can be established between the two publications in terms of the delimitation of the object of study, there are a series of elements that allow them to be distinguished, especially with regard to the methodological issue and the general approach.
Keywords: Contemporary Art; Artistic Creation; Globalization; Theoretical and artistic practices